LITERASI DIGITAL, MEMBEKALI ANAK DENGAN KEMAMPUAN DIGITAL - Hidayat, Fendi; Nurhatisyah; M. Fikry Ananda Syaheza; Feby Fauzi (Jurnal Pendekar Nusantara, 2024)
In the era of the Fourth Industrial Revolution, digital literacy becomes crucial in facing rapid technological changes. The digital literacy program at the "Istana Yatim Al-Jufri" Orphanage aims to enhance children's understanding and digital skills. Through training, interaction with parents, and the use of interactive learning resources, this program creates a safe learning environment in the digital age. Periodic evaluations are conducted to ensure the program's effectiveness, while collaboration with universities and communities helps enrich this initiative. This abstract also underscores the importance of digital literacy in addressing the negative impacts of the internet, such as the spread of hoaxes and unhealthy internet behavior. The community service activities organized by the Information Systems Study Program of the University of Batam and Universiti Teknologi Mara Cawangan Johor Malaysia aim to enhance the digital literacy of children and adolescents, focusing on wise and productive use of digital technology. In conclusion, the digital literacy program at the Orphanage has successfully increased understanding and community support for digital literacy, with recommendations to continue developing the program and increasing parental participation and digital access in the orphanage.